Handbook of research on emerging perspectives in intelligent pattern recognition, analysis, and image processing - Kamila, Narendra Kumar, 1967- (Hershey PA : Information Science Reference, 2016)
'This book discusses the advances of image processing and pattern analysis and addresses how new innovations will cater to the demands of daily life'--
Includes bibliographical references and index.
Keywords: Pattern recognition systems; Image processing -- Digital techniques; Computational intelligence